Swarm Intelligence Applied to Traffic Lights Group Formation - Oliveira, Denise de; Bazzan, Ana L. C. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2007)
Several traffic control approaches address the problem of reducing traffic jams. A class of these approaches deals with coordination of traffic lights to allow vehicles traveling in a given direction to pass an arterial without stopping. This paper presents an approach where each traffic light behaves like a social insect, having coordinated signals plan as tasks to be performed. The model uses a restricted communication mechanism and coordinated groups are formed in a dynamic way.